A educação musical à luz da ontologia do ser social - Costa, Yuri Coutinho Ismael da (2017)
One of the current and most important themes in music education research is diversity, which includes not only pedagogical ideas but also didactic action, the educational environments and the relationship between subjects (students, teachers and society as a whole) and musical cultures. A significant part of such researches adopts a relativistic and descriptive approach to phenomena, reading them according to their immediate connections and systemic limitations determined by present-day society. Given that the multiple instances of praxis are decisively influenced by the mode of production, i.e., by the characteristic form with which society organizes the labour processes, we propose to analyze the aforementioned diversity in the context of contemporary capitalism. As such, the main goal of the research is to demonstrate how the diversity of theories and practices of music education articulates with capitalist society and the ideological and pedagogical implications of such articulation to music education itself. As specific goals, we intend to: 1) understand the ontology of music education; 2) analyze the ways by which capital directly interferes in educational praxis; 3) identify the ideological tendencies, both critical and conservative, which lays the foundation of music education practice and research today; 4) verify the possibility of deducting new pedagogical and investigative alternatives from the adopted referential and performed analyses. We use historical and dialectical materialism as our research method, as it was originally developed and utilized by Karl Marx for the understanding of capitalism. Since this is an educational research, we also considered necessary to adopt a perspective which aims to reveal the immanent potentialities of development of individuals as singular members of humanity. Such perspective, the ontology of the social being, was elaborated by György Lukács based on the marxian theoretical framework. As a way to dialogue with the most upto-date theoretical tendencies in music education, we chose as our research universe two academic journals: the International Journal of Music Education and the Revista da ABEM (Associação Brasileira de Educação Musical). The critical analyses of papers is a fundamental process, since those are the most commonly used referential in teacher’s graduation courses, in comparison to academic theses, for example. As so, we chose to read all the papers published from 2008 – which is an important year, considering that it was back then that the current capitalist crises had begun – to 2014 in their entirety. From these readings, we selected for analyses those papers which more profoundly presented the studied themes. Results suggest, primordially, that the ideological influence of conservative political tendencies is extremely significant, mainly in accordance to the adoption of the discourse promoted by entities such as UNESCO and the World Bank. But we also learned that there are advancements in the comprehension of social being and how our society prevents it’s unrestricted development, and we also affirm the possibility to create new ways of action and research in music education from the ideas of the adopted referential.